Spatial-temporal distribution of atmospheric temperature anomalies connected with seismic activity in Tien-Shan - L G, SVERDLIK; S A, IMASHEV (MAUSAM, 2020)
In this paper we analyzed spatial-temporal temperature changes in the upper troposphere/lower stratosphere (UTLS) above the Northern and Central Tien-Shan detected by satellite remote sensing which have been compared against seismic activity in (1992-2015). These anomalous changes in temperature time series were used as pre-seismic indicators. Anomalous variation parameters were calculated accounting for amplitude and phase of short-time temperature variations at UTLS isobaric levels separated by the tropopause. The results show that the spatial structure and dynamics of temperature anomalies in the area of UTLS have a sufficiently stable relation to seismic activity. We estimated the spatial and time variability of anomalous temperature perturbations on the basis of 12 strongest earthquakes with magnitudes Mï5.0. The temperature anomalies were observed in all considered cases from 3 to 72 hours before the main seismic event.